Tag questions in English: linguistic features and possible padagogical implications - Bùi, Thị Ngọc Tuyền (ĐHNN, 2017)
Tag question is a special type of questions in English, which is frequently used by native speakers in daily conversations. However, students at Tran Phu High School, Quang Ninh Province usually make mistakes in using this grammatical structure so they cannot communicate successfully. This thesis is an attempt to help students master the nature of tag questions and become more confident in using them. In this thesis, the following points have been raised : the most relevant factors involving a tag question such as notions of tag questions, polarity, operators, intonation. Syntactic and semantic features of tag questions are also clearly presented. Besides, a study on students‟ mistakes in using tag questions is provided.The data were collected among 90 eleventh grade students at Tran Phu high school by means of questionnaires. The findings highlighted students‟ categories of mistakes including structural mistakes and intonation-related mistakes. Through the findings, the author has also tried to find out the causes of the mistakes and suggests some possible solutions in order to help students avoid committing these types of mistakes.